2019
DOI: 10.1016/j.dib.2019.104363
|View full text |Cite
|
Sign up to set email alerts
|

Data on genetic potentiality of folk rice (Oryza sativa L.) genotypes from Koraput, India in reference to drought tolerance traits

Abstract: Precise physiological and molecular marker-based assessment provides information about the extent of genetic diversity, which helps for effective breeding programmes. We have conducted detailed physiological and molecular marker-based assessment of selected eight indigenous rice landraces from Koraput, India along with tolerant (N22) and susceptible (IR64) check varieties under control and simulated drought stress using polyethylene glycol (PEG) 6000. After exposure to different levels of drought stress, relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Under this condition and less range of drought stress also, PTB-7, PTB-60 and PTB-35 were showed higher seedling vigour index. Similar study was conducted by Panda et al, (2019) and reported that among the folk rice genotypes of Odhisha, Nagina-22 showed highest seedling vigour index. Among the treatments, -5barPEG 6000 recorded the highest average proline content.…”
Section: Discussionsupporting
confidence: 80%
“…Under this condition and less range of drought stress also, PTB-7, PTB-60 and PTB-35 were showed higher seedling vigour index. Similar study was conducted by Panda et al, (2019) and reported that among the folk rice genotypes of Odhisha, Nagina-22 showed highest seedling vigour index. Among the treatments, -5barPEG 6000 recorded the highest average proline content.…”
Section: Discussionsupporting
confidence: 80%
“…The different response of brown rice genotype was caused by the characteristic of each genotype. The characteristic of plant is dominantly regulated by genetic factor [17]. According the result, Sikarujuik was the most susceptible genotype to Fe stress due to it underwent drastic decline in each Fe concentration.…”
Section: Discussionmentioning
confidence: 99%